Modeling the level of lactic acid for high performance athletes - Leminszka, M A; Dieck Assad, G; Martínez, S O; Garza, J E (Revista Mexicana de Ingenieria Biomedica, 2018)
The following article proposes a model to perform a non-invasive measurement of lactic acid. The model could be used effectively to measure lactic acid in high performance athletes. Several models are presented that intend to correlate measurable physical variables. The results indicate that the models predict effectively lactate quantities during physical tests applied to athletes. The best overall accuracy is provided by the ponderated-ideal-model. Comparing the results with blood test measurements from an electronic analyzer, the improvedideal-model obtains a maximum efficiency (accuracy) of 94.71%, while the basic-ideal-model obtains a minimum efficiency of 90.61%. Both models generate an error margin of around 5%. The efficiencies are indicative of how close the model can be to measurements performed by an electronic blood sample analyzer device.